2008
DOI: 10.1007/s10404-008-0363-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and flow test of long-term hydrophilic fluidic chip without using any surface modification treatment

Abstract: In order to effectively pump liquid in a fluidic chip, the PDMS or SU8 channels were frequently modified by surface treatments to obtain the hydrophilic surface but encountered the problem of the hydrophobic recovery. In this article, long-term highly hydrophilic fluidic chips were demonstrated using rapid fabrication of low-power CO 2 laser ablation and low-temperature glass bonding with an interlayer of liquid crystal polymer (LCP). The intrinsic hydrophilic materials of glass and LCP were beneficial for sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In addition, the contact angle decreased by another 10°after introduction of Pd(OAc) 2 . It is reported that the lower the contact angle, the higher the driving force (Chung et al 2009) for the flow inside a microchannel. Low contact angles of modified COC materials might be favorable for long-term self-driving of aqueous solution inside the channel.…”
Section: Resultsmentioning
confidence: 98%
“…In addition, the contact angle decreased by another 10°after introduction of Pd(OAc) 2 . It is reported that the lower the contact angle, the higher the driving force (Chung et al 2009) for the flow inside a microchannel. Low contact angles of modified COC materials might be favorable for long-term self-driving of aqueous solution inside the channel.…”
Section: Resultsmentioning
confidence: 98%
“…Laser ablation-based micromachining is gathering increasing attention because of its markedly faster prototyping speed, lower labor cost and higher level of automation. [26][27][28][29] The conditions for laser ablation of PDMS have been previously discussed by Liu et al 29 and Forgarty et al 30 In brief, features in the PDMS layer were designed using CorelDraw 10.0 and then engraved using VersaLaser VLS 3.50 with a 50 W CO 2 laser source (Universal Laser System Inc.) into either a 290 μm (for diode and metering chamber) or a 1.5 mm (for finger pump) thick commercial PDMS film (Rogers Corp.). The diode flap was formed by partially ablating the PDMS film, and the metering chambers were created by complete through-cutting in the same film (ESI, † section 1).…”
Section: Fabrication Of the Glass-pdms-glass (Gpg) Microfluidic Devicementioning
confidence: 99%
“…The results showed that a mixing performance of up to 90% could be obtained; even at low Reynolds numbers. CO 2 laser machining systems provide a low-cost and flexible means of patterning high-aspect microchannels on glass and polymer-based substrates (Yuan and Das 2007;Chung et al 2009Chung et al , 2010Huang et al 2009;Hong et al 2010;Yeh et al 2010). In developing a microfluidic chip for concentration detection applications, Klank et al (2002) showed that the characteristic Gaussian-like crosssection of the ablated microchannel was beneficial in aligning the optical fibers inserted into the chip following the bonding process.…”
Section: Introductionmentioning
confidence: 99%